Differential effects of immobilized CCL21 and ICAM1 on TILs with distinct expansion properties - Yado, Sofi; Zoabi, Rawan; Brezinger-Dayan, Karin; Albeck, Shira; Unger, Tamar; Meiron, Moran; Eisenberg, Galit; Nahmad, Alessio D.; Gilat, Aya Tzur; Besser, Michal J.; Geiger, Benjamin (Frontiers in Immunology, 2025)
Adoptive T cell therapy (ACT), particularly tumor-infiltrating lymphocyte (TIL)-based therapy holds great promise for cancer treatment, yet it still faces major challenges such as patient-to-patient variability in expansion rates and cytotoxic potency. Recent studies suggest that a “synthetic immune niche” (SIN), composed of immobilized CCL21 and ICAM-1, can enhance both the expansion and cytotoxicity of murine and patient-derived T cells. To explore the mechanisms underlying the variability of expansion and cytotoxic potency, we conducted morphological and molecular phenotyping of TIL specimens from different donors immediately following the pre-Rapid Expansion Protocol (pre-REP) stage, enabling us to predict their expansion potential. We further developed novel SIN-based strategies that differentially reinforce the efficacy of both low- and high-expanding TILs. Our experiments revealed two distinct TIL groups with either low- or high-proliferation properties, identified across cultures derived from different patients. We further demonstrate that a 14-day REP with feeder cells and SIN facilitates the proliferation of the low-expanding cells, while the expansion of high-expanding TILs benefits from a sequential expansion protocol, consisting of 7 days with feeder cells only, followed by 7 days with SIN treatment. At the end of the REP both TIL populations display high levels of granzyme B and perforin and reduced levels of exhaustion markers. Importantly, functional cytotoxicity assays using autologous tumor targets demonstrated that SIN stimulation improved the tumor-killing capacity of low-expanding TILs, while preserving the potent cytotoxicity of the high-expanding TILs. These data indicate that the refined CCL21+ICAM1 SIN treatment improves expansion rates and activation profiles of both TIL populations, thereby enabling a powerful, personalized SIN-enhanced protocol for TIL-based immunotherapy.